Chain of geoconservation in an Argentinian tourist development program: Fin del Mundo road as a case study - Coronato, Andrea Maria Josefa (2023)
The idea of a geoconservation chain is applied to the ‘End of the World Road’ which is part of an Argentinian tourist development program called La Ruta Natural (The Natural Road). To conduct a comprehensive and specific analysis, this itinerary was divided into six segments and sieved through the steps and substeps of the framework. The diagnosis step –carried out by multidisciplinary groups of academics turned out to be the most developed one whereas the conservation link of the chain was the weakest, lacking the participation of decision-makers, environmentalists, and legislators. In terms of promotion, success was largely achieved indirectly, after the intervention of educators and tourist entrepreneur, because the georesources analyzed are mainly used for tourism. The program highlights less than a third of the natural attractionsthat are already inventoried. If some of these attractions were incorporated into the itinerary, this could reinforce the use of the road and would make georesources more visible and so would become geoconservation targets. The case study presented here shows a reciprocal relationship between geoconservation and tourism. Wise use of the End of the World Road contributes to geoconservation and at the same time, geoconservation is essential for nature-based tourism.